2015
DOI: 10.1159/000381557
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Motor Cortex Stimulation in the Treatment of Chronic, Intractable Neuropathic Pain

Abstract: Background/Objectives: Although motor cortex stimulation (MCS) has been used for more than 20 years in the treatment of chronic neuropathic pain, there is still a debate about the efficacy of MCS. Methods: To investigate the long-term results and the factors associated with the long-term success of chronic MCS, 21 patients who underwent MCS trial were classified as having central poststroke pain, central pain after spinal cord injury (SCI) and peripheral neuropathic pain, and we investigated the clinical facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“… 5) There have been several reports of the long-term effects of MCS with more than 3.5 years of follow-up. 14 , 26 28) Im et al examined 21 patients with neuropathic pain who underwent MCS, and reported that the trial success rate was 76.2%, with long-term effects achieved in 52.4% during 53 ± 39 months of follow-up. 26) These results are compatible with our current findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5) There have been several reports of the long-term effects of MCS with more than 3.5 years of follow-up. 14 , 26 28) Im et al examined 21 patients with neuropathic pain who underwent MCS, and reported that the trial success rate was 76.2%, with long-term effects achieved in 52.4% during 53 ± 39 months of follow-up. 26) These results are compatible with our current findings.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 26 28) Im et al examined 21 patients with neuropathic pain who underwent MCS, and reported that the trial success rate was 76.2%, with long-term effects achieved in 52.4% during 53 ± 39 months of follow-up. 26) These results are compatible with our current findings. Predictive factors associated with long-term effects of MCS are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andre‐Obadia et al reported that half of the patients in one study ( n = 10) showed a significant benefit after two to nine years of continuous MCS therapy. Im et al considered MCS to be more effective in the treatment of CPSP based on long‐term follow‐up (53 ± 39 months) compared to pain due to spinal cord injury. A loss of efficacy was reported based on long‐term follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for the simultaneous implantation of electrodes for DBS and MCS are described in detail in our previous reports regarding the surgical treatment of refractory neuropathic pain [16][17][18][19][20] . After we took stereotactic magnetic resonance images (MRI-Achieva 1.5T, Phillips, Eindhoven, the Netherlands), we transferred the obtained imaging data to the surgical navigation system, which was used to define the target coordinates of the Vc and the precentral hand knob (Figure 1a).…”
Section: Localization Of Anatomical Targets and Electrode Implantationmentioning
confidence: 99%